Faktor-Faktor yang Berpengaruh terhadap Brand Image ditinjau dari Komunikasi Pemasaran - Hardyansyah, Robby; selviana, Inggrid; Budiputranto, Radhitya (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to describe each influence of the marketing mix starting from public relations advertising, personal selling, public relations and direct marketing on a company's brand image. This research uses literature review techniques with a descriptive qualitative approach. Search for literature using the Google search engine and Google Scholar with the keywords "marketing communications", "brand image awareness", "factors influencing brand image awareness", "brand image and marketing communications". The literature sought is journals, books, conference proceedings, and so on to be analyzed critically and explain what is found in each piece of literature. The research results show that the factor that influences brand image is implementing marketing communication strategies. A marketing communications strategy can create marketing information that provides value according to a comprehensive company plan. The factors that influence a good marketing strategy are marketing communication, where marketing communication is not only about promotion, but there are important elements or communication mix, namely advertising, sales promotion, personal selling, public relations and direct marketing. These five elements can influence the brand image of a company so that the company can increase sales of a product.